Evaluation of the effects of different chemical pretreatments in sugarcane bagasse on the response of enzymatic hydrolysis in batch systems subject to high mass loads. (March 2021) - Paz-Cedeno, Fernando Roberto; Henares, Lucas Ragnini; Solorzano-Chavez, Eddyn Gabriel; Scontri, Mateus; Picheli, Flávio Pereira; Miranda Roldán, Ismael Ulises; Monti, Rubens; Conceição de Oliveira, Samuel; Masarin, Fernando
Abstract: In the present study, sugarcane bagasse (SB) was subjected to different pretreatments. The pretreated SB was characterized chemically and structurally and was enzymatically hydrolyzed using a commercial enzyme preparation. Pretreatment with sulfite-NaOH was the most efficient for removing lignin while keeping cellulose intact. In addition, sulfite-NaOH pretreatment presented the best response to the enzymatic hydrolysis of cellulose and xylan, reaching conversions of 90%. The increase in consistency (≥10%) in the enzymatic hydrolysis of SB pretreated with sulfite-NaOH showed a loss of cellulose and xylan conversions efficiencies of 28 and 37%, respectively. However, enzymatic hydrolysis with a consistency of 20% resulted in a maximum rate of glucose and xylose formation of 8.5 and 3.0 g L −1  h −1, respectively, and an enzymatic hydrolysate containing 80 and 33 g L −1 of glucose and xylose, respectively. The enzymatic hydrolysis assay in a bioreactor with 20% consistency promoted faster liquefaction of SB, resulting in a higher maximum rate of glucose production (10.6 g L −1  h −1 ). The increase in the concentration and rate of formation of fermentable sugars in the enzymatic hydrolysate can partially avoid steps of concentration of the hydrolysate, resulting in less energy consumption and greater productivity of the bioproducts obtained from the hydrolysate, such as cellulosic ethanol (2G ethanol). Graphical abstract: Image 1 Highlights: Pretreatment of sugarcane bagasse with sulfite-NaOH efficiently removed lignin. Pretreatment with sulfite-NaOH had the strongest effect on the enzymatic hydrolysis. Enzymatic hydrolysis under high consistency resulted in hydrolysate rich in sugars. Enzymatic hydrolysis performed in bioreactor show maximum rate of glucose increased.